Inequality of Opportunity in Mexico - Vélez Grajales, Roberto; Monroy-Gómez-Franco, Luis A.; Yalonetzky, Gastón (Journal of Income Distribution®, 2019)
Mexico is a country with high levels of inequality and low intergenerational social-mobility rates for those located at the bottom extremes of the wealth distribution. Although such low rates suggest that at least a share of the observed income inequality may be due to an unequal distribution of opportunities, this conjecture has not been thoroughly tested in the literature. The present article fills this gap estimating the lower bound of the contribution of unequal opportunities to income and wealth inequality in Mexico, with an operationalization of the “ex-ante” approach to the measurement of inequality of opportunity. Relying on a national representative survey designed for the analysis of social mobility, namely, the ESRU Survey on Social Mobility in Mexico (2011), we are able to define a broad set of circumstance groups (“types”), encompassing the wealth of the household of origin. This available information reduces the omitted variable bias of previous estimations and allows for a better account of the role of inequality of opportunity in income inequality. Our results show that the lower bound of the contribution of unequal opportunities to total income inequality and total wealth inequality is around 30 per cent, which is substantially higher than previous estimations for Mexico and ranks among the highest values in Latin America.